2021
DOI: 10.1096/fj.202100376rr
|View full text |Cite
|
Sign up to set email alerts
|

Novel lncRNA‐HZ04 promotes BPDE‐induced human trophoblast cell apoptosis and miscarriage by upregulating IP3R1/CaMKII/SGCB pathway by competitively binding with miR‐hz04

Abstract: Normal pregnancy is essential for human reproduction. However, BaP (benzo(a)pyrene) and its metabolite BPDE (benzo(a)pyrene‐7,8‐dihydrodiol‐9,10‐epoxide) could cause dysfunctions of human trophoblast cells and might further induce miscarriage. Yet, the underlying mechanisms remain largely unknown. Herein, we identified a novel upregulated lnc‐HZ04 and a novel downregulated miR‐hz04 in villous tissues of unexplained recurrent miscarriage (RM) relative to those in healthy control tissues and also in BPDE‐treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…In polycystic ovary syndrome (PCOS), lncRNA MALAT1 reduction could suppress TGFb signaling through sponging miR-125b and miR-203a in granulosa cells (41). In unexplained recurrent spontaneous abortion, circRNA-DURSA/ miR-760/HIST1H2BE axis, lncRNA-HZ04/miR-hz04/BPDE axis, and lncHZ05/miR-hz05/BPDE axis were proved to affect human trophoblast cell proliferation and apoptosis (42)(43)(44). In preeclampsia, lnc00511 was functioned as a molecular sponge for miR-29b-3p, antagonizing its ability to repress Cyr61 protein translation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In polycystic ovary syndrome (PCOS), lncRNA MALAT1 reduction could suppress TGFb signaling through sponging miR-125b and miR-203a in granulosa cells (41). In unexplained recurrent spontaneous abortion, circRNA-DURSA/ miR-760/HIST1H2BE axis, lncRNA-HZ04/miR-hz04/BPDE axis, and lncHZ05/miR-hz05/BPDE axis were proved to affect human trophoblast cell proliferation and apoptosis (42)(43)(44). In preeclampsia, lnc00511 was functioned as a molecular sponge for miR-29b-3p, antagonizing its ability to repress Cyr61 protein translation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we have identified that inhibition in trophablast cell proliferation, migration/invasion or the increase in trophoblast cell apoptosis is associated with RM. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] However, whether other dysfunctions of human trophoblast cells might also induce miscarriage should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 ] Increasing studies have shown that trophoblast cell functions are regulated by certain lncRNAs, such as lncRNA EPB41L4A‐AS1 which induces metabolic reprogramming in trophoblast cells and placenta tissue, [ 37 ] lnc‐SLC4A1‐1 which epigenetically regulates unexplained recurrent pregnancy loss by activating CXCL8 and NF‐kB pathway, [ 38 ] and lncRNA MEG8 which causes trophoblast dysfunctions and miscarriage by decreasing cell proliferation and invasion. [ 39 ] In this group, we identified a number of novel lncRNAs, including lnc‐HZ01, [ 12 ] lnc‐HZ03, [ 7 ] lnc‐HZ04, [ 10 ] lnc‐HZ05, [ 11 ] lnc‐HZ08, [ 8 ] lnc‐HZ09, [ 15 ] and lnc‐HZ14, [ 13 ] which regulate various trophoblast cell dysfunctions and the occurrence of miscarriage. Meanwhile, it has been reported that lncRNAs could also regulate HR repair.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Recently, we have performed transcriptome sequencing of unexplained RM and HC villous tissues and BPDE-treated trophoblast Swan 71 cells. 28 Based on these sequencing data, we identified a number of novel lncRNAs of interest, including lnc-HZ01, which was found to regulate BPDE-suppressed trophoblast cell proliferation and miscarriage by forming a lnc-HZ01/MXD1 feedback loop 29 ; lnc-HZ03, which up-regulated p53/SAT1 pathway to promote trophoblast apoptosis and affected miscarriage 28 ; lnc-HZ04, which served as a ceRNA for miR-hz04 and up-regulated the pathway 30 ; and lnc-HZ08, which regulated BPDE-induced trophoblast cell dysfunctions and was associated with miscarriage. 31 These works illustrate that these lncRNAs are closely associated with the occurrence of miscarriage.…”
Section: Introductionmentioning
confidence: 99%